Rational selection of alternative, environmentally compatible surfactants for biotechnological production of pharmaceuticals—A step toward green biotechnology. (1st August 2014) - Straub, Jürg Oliver; Shearer, Russel; Studer, Martin
Abstract The biotechnological production of pharmaceutical active substances needs ancillary substances. Surfactants are used at the end of the cell culture as a protection against potential viral or bacterial contamination and to lyse the producing cells for isolation and purification of the products. To find a replacement for a surfactant that had raised environmental concern, environmentally relevant data for potential alternatives were searched for in the literature. Significant data gaps were filled with additional tests: biodegradability, algal growth inhibition, acute daphnid immobilization and chronic daphnid reproduction toxicity, acute fish toxicity, and activated sludge respiration inhibition. The results were used to model removal in the wastewater treatment plants (WWTPs) serving 3 biotechnological production sites in the Roche Group. Predicted environmental concentrations (PECs) were calculated using realistic amounts of surfactants and site‐specific wastewater fluxes, modeled removals for the WWTPs and dilution factors by the respective receiving waters. Predicted no‐effect concentrations (PNECs) were derived for WWTPs and for both fresh and marine receiving waters as the treated wastewater of 1 production site is discharged into a coastal water. This resulted in a spreadsheet showing PECs, PNECs, and PEC ÷ PNEC risk characterization ratios for the WWTPs and receiving waters for all investigated surfactants and all 3 sites. This spreadsheet now serves as a selection support for the biotechnological developers. This risk‐based prioritization of surfactants is a step toward green biotechnological production. Environ Toxicol Chem 2014; 33:2140–2146. © 2014 SETAC